Germplasm development - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1980)
The cassava germplasm section of the Centro Internacional de Agricultura Tropical has developed a multi-stage genetic improvement procedure involving: (1) evaluation of germplasm accessions in various environments for possible recommendations as new cv. or as parents in a hybridization program; (2) formation of broad-based gene pools with high levels of resistance and/or adaptation in specific environments; (3) assure acceptability of the final product by producers, processors, and consumers. (CIAT)